Popular Culture as Pedagogy : Teaching “Il Canto di Ulisse” from Dante to Jovanotti in the American College Classroom - Marzia Caporale (Perspectives Médiévales)
This article explores the challenges of teaching Dante’s Divine Comedy to contemporary American college students. In particular, the study addresses the role of subtext that the “Canto di Ulisse” plays to rap-pop artist Jovanotti’s song “Bruto” (Album : Buon Sangue, 2005) and to director Emanuele Crialese’s film Terraferma (2011). It further argues that the gap between “high” and “low” culture can be bridged by adopting alternative pedagogical tools (e.g., blogging, Twitter) to be used in the classroom.